A companion to cultural studies - Miller, Toby 1958- (Malden, Mass. Blackwell, 2001)
This volume brings together the latest work in cultural studies, providing a synopsis of critical trends. It is designed to stimulate debate even as it acts as an introduction. It asks the question: what is cultual studies and what is not?
Table of contents 1. What it is and what it isn't : introducing cultural studies Toby Miller -- 2. Interdisciplinary Mark Gibson and Alec McHoul -- 3. Is there a cultural studies of law Rosemary Coombe -- 4. The renewal of the cultural in sociology Randy Martin -- 5. Sociology, cultural studies, and disciplinary boundaries Frank Webster -- 6. Notes on the traffic between cultural studies and science and technology studies Marianne de Laet -- 7. Political economy within cultural studies Richard Maxwell -- 8. Cultural studies and philosophy : an intervention Douglas Kellner -- 9. "X" never, ever marks the spot : archaeology and cultural studies Silke Morgenroth -- 10. The unbalanced reciprocity between cultural studies and anthropology George E. Marcus -- 11. Media studies and cultural studies : a symbiotic convergence John Nguyet Erni -- 12. Comparative cultural studies traditions : Latin America and the US George Yúdice -- 13. Can cultural studies speak Spanish Jorge Mariscal -- 14. Australasia Graeme Turner -- 15. Peripheral vision : Chinese cultural studies in Hong Kong Eric Kit-wai Ma -- 16. Decentering the centre : cultural studies in Britain and its legacy Ben Carrington -- 17. European cultural studies Paul Moore -- 18. Let's get serious : notes on teaching youth culture Justin Lewis -- 19. Looking backwards and forwards at cultural studies Paul Smith -- 20. Close encounters : sport, science, and political culture C.L. Cole -- 21. Intellectuals, culture, policy : the practical and the critical Tony Bennett -- 22. Listening to the state : culture, power, and cultural policy in Columbia Ana María Ochoa Gautier -- 23. Museum highlights : a gallery talk Andrea Fraser -- 24. The scandalous fall of feminism and the "first Black president" Melissa Deem -- 25. Rap and feng shui : on ass politics, cultural studies, and the timbaland sound Jason King -- 26. Fashion Sarah Berry -- 27. Cultural studies and race Robert Stam -- 28. Globalization and culture Toby Miller
Includes bibliographical references (pages 531-552) and index.
Keywords: Culture -- Study and teaching